Mathematical formulation of the problem of designing a transport vessel, in the conditions of transition to a Blue Economy - Yegor Petrov (CV. Media Digital Publikasi Indonesia, 2024)
When setting a task for designing a vessel, restrictions imposed by the customer, classification societies and requirements for the characteristics of ship structures are usually taken into account. In the current conditions, it also becomes necessary to ensure sufficient